A legally‐informed definition of volunteering in nonprofits and social enterprises: Unpaid work meets profit motives. Issue 3 (16th October 2021) - Overgaard, Charlotte; A. Kerlin, Janelle
Abstract: This article presents a definition of volunteering that will help organizations and workers, especially those engaged in commercial activity for a social purpose, determine when U.S. organizations can legally draw on volunteer labor. By drawing on recent U.S. court cases, the intentions of the Fair Labor Standards Act (FLSA) to protect vulnerable workers and the wider framing literature on organizational logics, work, and volunteering, we outline under which circumstances workers are considered employees rather than volunteers and therefore covered by the FLSA and entitled to minimum pay. We show that in order to determine the legalities of work under current law, it is necessary, but not sufficient, to consider whether activities are carried out for commercial purposes. What matters most for a legally‐informed definition is the role performed within organizations and the promises made to individual workers in terms of compensation.